2008
DOI: 10.1021/nl080129n
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Growth of Ternary Alloy Nanowires Using Metalorganic Chemical Vapor Deposition

Abstract: We report the growth and characterization of ternary AlxGa1- xAs nanowires by metalorganic chemical vapor deposition as a function of temperature and V/III ratio. Transmission electron microscopy and energy dispersive X-ray spectroscopy show that, at high temperatures and high V/III ratios, the nanowires form a core-shell structure with higher Al composition in the nanowire core than in the shell. We develop a growth model that takes into account diffusion of reactants and decomposition rates at the nanowire c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 37 publications
4
89
1
2
Order By: Relevance
“…One goal is to have the ability to control the composition of semiconductor alloys and effectively tune the band-gap of a material for a specific function. As a result, various ternary alloys have recently attracted a great deal of attention for their ability to achieve a wide range of band-gaps, [1][2][3][4][5][6][7][8][9][10][11][12] Additionally, nano-materials, such as nano-wires and nano-ribbons, offer greater versatility by providing a wider range of alloy composition and band-gap modulation which is unachievable using traditional epitaxial film materials due to lattice strain at the substrate interface. 13 Ternary chalcogenide semiconductors, particularly cadmium sulpho-selenide (CdS x Se 1Àx ) alloys, have been intensely studied 8,[14][15][16][17][18][19] in part due to the remarkably broad range of stable stoichiometries that can be attained, owing to the small lattice mismatch among the constituent anions.…”
Section: Introductionmentioning
confidence: 99%
“…One goal is to have the ability to control the composition of semiconductor alloys and effectively tune the band-gap of a material for a specific function. As a result, various ternary alloys have recently attracted a great deal of attention for their ability to achieve a wide range of band-gaps, [1][2][3][4][5][6][7][8][9][10][11][12] Additionally, nano-materials, such as nano-wires and nano-ribbons, offer greater versatility by providing a wider range of alloy composition and band-gap modulation which is unachievable using traditional epitaxial film materials due to lattice strain at the substrate interface. 13 Ternary chalcogenide semiconductors, particularly cadmium sulpho-selenide (CdS x Se 1Àx ) alloys, have been intensely studied 8,[14][15][16][17][18][19] in part due to the remarkably broad range of stable stoichiometries that can be attained, owing to the small lattice mismatch among the constituent anions.…”
Section: Introductionmentioning
confidence: 99%
“…Следует отметить, что подобное образование самоорганизован-ной структуры типа " стержень-оболочка" ранее упоми-налось как при МПЭ [8], так и газофазной эпитаксии [9]. Однако приведенные результаты противоречат друг дру-гу.…”
Section: номинальныйunclassified
“…Однако приведенные результаты противоречат друг дру-гу. Так, в первом случае, как и в данной работе, мольный состав x у оболочки был выше, чем у стержня, в то время как в работе [9] -наоборот. Детальный анализ причин, приводящих к подобному феномену, приведен в отдельной статье [10].…”
Section: номинальныйunclassified
“…Today the MOVPE self-assembly of III-V nanowires is studied by several research groups, which however, in most cases use colloidal Au NPs as catalysts for the VLS growth. To date the Au-catalyst assisted MOVPE of III-V nanowires has been extended to ternary alloys, such as GaAsP , GaInP (Sköld et al, 2005), and InGaAs (Regolin et al, 2006), while only few data can yet be found on the catalyst-assisted MOVPE of AlGaAs nanowires (Lim et al, 2008). For these ternary alloys a major challenge is to growth nanowires with uniform composition along both their major axis and in the radial direction (Regolin et al, 2006;Kim et al, 2006;& Lim et al, 2008).…”
Section: Iii-v Nanowires Grown By Au-catalyst Assisted Movpementioning
confidence: 99%
“…To date the Au-catalyst assisted MOVPE of III-V nanowires has been extended to ternary alloys, such as GaAsP , GaInP (Sköld et al, 2005), and InGaAs (Regolin et al, 2006), while only few data can yet be found on the catalyst-assisted MOVPE of AlGaAs nanowires (Lim et al, 2008). For these ternary alloys a major challenge is to growth nanowires with uniform composition along both their major axis and in the radial direction (Regolin et al, 2006;Kim et al, 2006;& Lim et al, 2008). The MOVPE growth of nanowires with modulation of the material composition in either the axial or radial direction has been also demonstrated for a number of III-V systems.…”
Section: Iii-v Nanowires Grown By Au-catalyst Assisted Movpementioning
confidence: 99%